2011
DOI: 10.1002/jpln.201000108
|View full text |Cite
|
Sign up to set email alerts
|

Reintroduction of a native Glomus to a tropical Ultisol promoted grain yield in maize after fallow and restored the density of arbuscular mycorrhizal fungal spores

Abstract: Maize (Zea mays L.) is an important crop in central Thailand where fallow is widely practiced and farmers are interested in crop rotation and beneficial soil biota. A pot experiment using a Typic Paleustult (topsoil + subsoil) from the National Corn and Sorghum Research Centre, Nakhonratchasima Province, Thailand was undertaken over three successive crops to evaluate effects of agronomic practices on populations of arbuscular mycorrhizal (AM) fungi and to determine whether reintroduction of a local Glomus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…were chosen. These AM species were dominant species in this soil and the previous study showed that they were sensitivity to Brassica crop [10]. The two Brassica have different types of ITC.…”
Section: Introductionsupporting
confidence: 56%
“…were chosen. These AM species were dominant species in this soil and the previous study showed that they were sensitivity to Brassica crop [10]. The two Brassica have different types of ITC.…”
Section: Introductionsupporting
confidence: 56%